Pop song : adventures in art and intimacy - Pham, Larissa (Catapult, 2021)
"Like a song that feels written just for you, Larissa Pham's debut work of nonfiction captures the imagination and refuses to let go. Pop Song is a book about distances, near and far. The miles we travel to get away from ourselves, or those who hurt us, and the impossible gaps that can exist between two people sharing a bed. Plumbing the well of culture for clues and patterns about love and loss-from Agnes Martin's abstract paintings to James Turrell's transcendent light works, and Anne Carson's Eros the Bittersweet to Frank Ocean's Blonde-Pham writes of her youthful attempts to find meaning in travel, sex, drugs, and art before sensing that she might need to turn her gaze upon herself. There is heartache in these pages, but Pham's electric ways of seeing create a perfectly fractured portrait of modern intimacy that is triumphant in its vulnerability and restlessness. Pop Song is a book about all the routes by which we might escape our own needs before finally finding a way home"--